The Family-Check-Up® Autism Implementation Research (FAIR) Study: protocol for a study evaluating the effectiveness and implementation of a family-centered intervention within a Canadian autism service setting - Teresa Bennett; Teresa Bennett; Irene Drmic; Julie Gross; Marc Jambon; Melissa Kimber; Anat Zaidman-Zait; K. Andrews; Julia Frei; E. Duku; Stelios Georgiades; Andrea Gonzalez; et al. (Frontiers Media S.A., 2024)
IntroductionPrevalence rates of emotional and behavior problems (EBP) in autistic children and youth are high (40-70%), and often cause severe and chronic impairment. Furthermore, autistic children are also more likely to experience family "social-ecological" adversity compared to neurotypically developing peers, including social isolation, child maltreatment, caregiver mental illness, and socioeconomic risk. These family stressors increase the risk of co-occurring EBP among autistic children and can often impede access to evidence-based care, thus amplifying long-term health inequities for autistic children and their caregivers. In the current autism services landscape, there are few scalable, evidence-based programs that adequately address these needs. The Family Check-Up (FCU®) is a brief, strength-based, and tailored family-centered intervention that supports positive parenting and explicitly assesses the social determinants of child and family mental health within an ecological framework. Studies have demonstrated long-term positive child and caregiver outcomes in other populations, but the FCU® has not been evaluated in families of autistic children and youth. Therefore, we aimed to evaluate FCU® implementation within an established, publicly funded Autism Program in Ontario, Canada, with delivery by autism therapists, to demonstrate sustainable effectiveness within real-world settings.MethodsIn this study, we outline the protocol for a hybrid implementation-effectiveness approach with two key components: (1) A parallel-arm randomized controlled trial of N = 80 autistic children/youth (ages 6-17 years) and high levels of EBP and their caregivers. Primary and secondary outcomes include child EBP, and caregiver well-being and parenting. (2) A mixed methods implementation study, to describe facilitators and barriers to implementation of the FCU® within an autism service setting.DiscussionScalable, ecologically focused family-centered interventions offer promise as key components of a public health framework aimed at reducing mental health inequities among autistic children, youth, and their caregivers. Results of this study will inform further program refinement and scale-up.